Differences in structural brain morphometry between musicians and non-musicians - Liu, Ying; Huang, Qilin; Hosseini, Thomas; Hou, Jiancheng (Frontiers in Human Neuroscience, 2025)
ObjectiveAlthough music has been shown to affect brain function, the structural characteristics of the brain in musicians compared to non-musicians are often overlooked. This limited attention restricts the practical use of music’s emotional, cognitive, and motor functions. The current study aimed to investigate structural differences in the brains of musicians compared to non-musicians in order to better understand the neuroanatomical basis of musical training.MethodsSixteen musicians and seventeen age-matched non-musicians underwent a brain structural neuroimaging scan. Group differences in structural morphometry were assessed.ResultsSignificant differences were found in cortical thickness, fractal dimensionality, gyrification, and sulcal depth measures. Compared to non-musicians, musicians showed greater cortical thickness in the left superior frontal gyrus and right central parietal region, and showed structural advantages in fractal dimensionality and sulcal depth in the left fusiform gyrus and right central region. In contrast, non-musicians showed greater gyrification in the bilateral insula, right superior parietal lobule, and right supramarginal gyrus. Notably, significant interactive effects were observed between gender and cortical thickness, fractal dimensionality, gyrification, and sulcal depth in regions of the limbic system, including the hippocampus, cingulate gyrus, insula, fusiform gyrus, and precuneus.ConclusionStructural differences in the frontal cortex, limbic system, and sensorimotor areas between musicians and non-musicians highlight the changes in brain structure associated with musical training. These findings provide insight into the underlying mechanisms of music-related brain function and may provide guidance for future applications of music to improve mental health and neuroplasticity.